Analysis of the Influence of Good Corporate Governance on Company Value in All Manufacturing Companies Listed On Idx 2018-2020 - Julio Andre; Titiek Suwarti (Budapest International Research and Critics University, 2022)
This study aims to test the effect of Good Corporate Governance to Price to Book Value of All Registered Manufacturing Companies in Indonesia Stock Exchange from 2018-2020. Type of data used in this study is secondary data. The population of this study is all manufacture companies listed in Indonesia Stock Exchange from 2018-2020. To retrieve the sample, the writer employed purposive sampling method and applied criteria listed in Indonesia Stock Exchange, reported annually subsequently from 2018-2020 in Indonesia Stock Exchange and there was Managerial ownership, Institutional ownership, Independent commissioner, Audit committee, and frequency of board commissioners meeting in the company. The result of this study shows that Managerial ownership, Institutional ownership, Independent commissioner, Audit committee and frequency of board commissioners meeting positively and significantly influenced Price to Book Value in Manufacture company in Indonesia from 2018-2020.